2021
DOI: 10.1001/jamaneurol.2020.4986
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Blood Phosphorylated Tau181 and Neurofilament Light Chain With Neurodegeneration in Alzheimer Disease

Abstract: IMPORTANCEPlasma phosphorylated tau at threonine 181 (p-tau181) has been proposed as an easily accessible biomarker for the detection of Alzheimer disease (AD) pathology, but its ability to monitor disease progression in AD remains unclear.OBJECTIVE To study the potential of longitudinal plasma p-tau181 measures for assessing neurodegeneration progression and cognitive decline in AD in comparison to plasma neurofilament light chain (NfL), a disease-nonspecific marker of neuronal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 56 publications
14
175
4
3
Order By: Relevance
“…Additionally, Plasma pThr181 has diagnostic value and can differentiate AD from other neurodegenerative diseases such as FTLD with 70–80% sensitivity and specificity [ 128 ]. A longitudinal prospective study tracked a cohort of 1113 participants with follow up 8 years later and found that plasma pThr181 tau levels is associated with progressive decline in cognitive symptoms and brain atrophy [ 130 ]. This association was also found in patients with MCI, suggesting that plasma pThr181 could be an early predictor of neurodegeneration and cognitive decline.…”
Section: Main Textmentioning
confidence: 99%
“…Additionally, Plasma pThr181 has diagnostic value and can differentiate AD from other neurodegenerative diseases such as FTLD with 70–80% sensitivity and specificity [ 128 ]. A longitudinal prospective study tracked a cohort of 1113 participants with follow up 8 years later and found that plasma pThr181 tau levels is associated with progressive decline in cognitive symptoms and brain atrophy [ 130 ]. This association was also found in patients with MCI, suggesting that plasma pThr181 could be an early predictor of neurodegeneration and cognitive decline.…”
Section: Main Textmentioning
confidence: 99%
“…Similarly, O'Connor et al [145] observed, in their longitudinal study of FAD, that plasma p-tau 181 concentrations were higher in mutation carriers than non-carriers from 16 years prior to estimated symptom onset. Furthermore, Moscoso et al [146] have recently shown that longitudinal changes in plasma p-tau 181 are associated with longitudinal neurodegeneration in AD-specific brain regions, as measured by FDG-PET and grey matter volume. Together, this evidence suggests plasma p-tau 181 poses a promising blood-based biomarker for both AD diagnosis and for patient recruitment into clinical trials.…”
Section: P-tau181 217 and 231 As Tau Biomarkers In Bloodmentioning
confidence: 99%
“…Nine studies that used Simoa or MSD methods were included for the analysis of normal range of plasma ptau181. Six publications, reporting seven cohorts, were retrieved using the Simoa technology [45,[84][85][86][87][88], including 1424 healthy subjects. The ES for plasma ptau181 levels in healthy populations was 11.18 pg/ml (95% CI 9.68-12.68, I 2 = 95.9%, P < 0.0001, Fig.…”
Section: Study Inclusions and Quality Assessmentmentioning
confidence: 99%